Urbanization Processes in the Context of Spatial Development Patterns of Municipalities in the Zone of Influence of Megacities - Okrepilov Vladimir V.; Kuznetsov Sergey V.; Mezhevich Nikolai M.; Sviridenko Marina V. (Economic and Social Changes: Facts, Trends, Forecast, 2019)
In the modern world, urbanization processes have become global and comprehensive. The federal law on regional policy “Fundamentals of the state policy of regional development in the Russian Federation for the period up to 2025” points out that the development of agglomerations is the most important condition for ensuring the competitiveness of the economy of the Russian regions and for providing economic growth and technological breakthrough. It can be stated that the significant role of the development of megacities as drivers of national economic growth is officially declared at the federal level of management of socio-economic development of territories. Due to the presence of various modifications of the organization of the economic space of the global economy in recent years, it becomes relevant to find new directions of scientific fundamental and applied research, the subject of which should be the socio-economic mechanisms of functioning of megacities and urban agglomerations formed on their basis, as well as the study of their impact on the municipal, regional, national and world economy in the context of globalization. In order to achieve a high degree of effectiveness in applying the experience of the United States, Western and Eastern Europe in our country, it is necessary to interpret the results of international activities in a certain context while maintaining the main target parameters. International processes of urbanization in the Russian practice are undergoing significant changes and are implemented in the form of suburbanization, a slightly different interpretation of the Western experience. Some of the results of the analysis of the activity of agglomeration movement in the Russian and international practice show that our country is lagging behind other countries, which is reflected in the presence of an insufficient number of municipalities that are larger and more populous then agglomerations: conurbations and others. We see the most important task of further research in studying the theory of urbanization and the processes of spatial and socio-economic development occurring in the territory of municipalities adjacent to the boundaries of megacities